(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research article examines the transformative power of feminist discourse in literature, focusing on its capacity to empower individuals and challenge existing patriarchal structures. Through an analysis of prominent feminist texts and the exploration of key themes such as identity, agency, and resistance, this article highlights how literature serves as a platform for feminist discourse, amplifying marginalized voices and fostering social change. By reclaiming narratives, feminist literature empowers readers, inspiring them to question gender norms, promote equality, and imagine alternative futures. This article underscores the significance of feminist discourse in literature and its potential to shape perceptions, challenge oppressive systems, and advocate for a more inclusive society.